Os estudantes do PROEJA no IFRN: a contribuição de seus arranjos culturais para a permanência no Curso Técnico de Nível Médio Integrado em Alimentos - Ferreira, Rejane Gomes (2014)
This research looked for clues aiming any success achieved by students from Curso Técnico de Nível Médio Integrado em Alimentos, Young and Adults Educations mode (PROEJA), at Instituto Federal de Educação, Ciência e Tecnologia -IFRN -Campus Currais Novos. Aware about adversity levels in institutional, socioeconomic, pedagogical, didactical and personal aspects, which reflects in students abandonment from this course, this case study, in popular education scope, attempted to stay away from failure situations, systematically pointed in PROEJA courses. To get close of its objective, side by side with the risk of privileging individual merits, or the jargon "if you want, you can", this work searched for clues on the answers from the students, in an upside down way, which were capable to project them as protagonists, taking support basically in their most relevant and less valued cultural arrangements. Took emphasis students relationshipment capacity, and some teachers, when they get attached to support groups, in a way that allowed them to surpass adversities and conquer their goals, studying together and with a great sacrifice. This research has as subjects students who have concluded Curso Técnico de Alimentos, professors and managers. The research starts from a qualitative approach, with exploratory nature, characterizing as case study. To collect the data techniques semi-structured interviews were used. Results point that the students permanency in Curso Técnico em Alimentos can be strengthened with institutional support, pedagogical and didactical practices more capable to worry with students in their learning process, and in their fight against difficulties already listed by this and others researches. If the relational aspects strongly pointed by PROEJA students doesn't solve the problems, they can generate an investigative didactical and pedagogical action, more able to detect, in each step, the problems threatening their permanency, and that will emerge, as happened in the best popular educ their permanency, and that will emerge, as happened in the best popular education experiences, chased by civil-military dictatorship.